2013
DOI: 10.5530/ijper.47.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Rapidly Disintegrating Tablets of Racecadotril with Enhanced in-vitro Dissolution Achieved by Solid Dispersion Technique

Abstract: The objectives of present investigations were to enhance dissolution rate of irbesartan by using chitosan and chitosan chlorhydrate and optimize an effective concentrations of both.Cocrystals of irbesartan (IB) were prepared by solvent change technique.Chitosan solution was prepared by soaking chitosan and chitosan chlorhydrate in glacial acetic acid. A weighed amount of drug was dispersed in chitosan solution by stirring. The dispersion was added to sodium citrate solution to precipitate 0 chitosan on drug cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…An excess amount of cocrystals were added to the flask containing distilled water. The solutions were vortexed for 2 min and placed on a rotary shaker at 100 rpm and 27±0.5° for 24 h. After equilibrium, the solution was filtered through Whatman filter paper (#41) and the concentration of drug was determined spectrophotometrically at λ max 378 nm [21] .…”
Section: Preparation and Evaluation Of Cocrystalsmentioning
confidence: 99%
“…An excess amount of cocrystals were added to the flask containing distilled water. The solutions were vortexed for 2 min and placed on a rotary shaker at 100 rpm and 27±0.5° for 24 h. After equilibrium, the solution was filtered through Whatman filter paper (#41) and the concentration of drug was determined spectrophotometrically at λ max 378 nm [21] .…”
Section: Preparation and Evaluation Of Cocrystalsmentioning
confidence: 99%
“…Previous research studied the use of wet granulation to produce meloxicam ODT (Kulkarni et al, 2010), the use of sublimation (Elbary et al, 2012) and solid dispersion (Singhvi et al, 2013) methods to increase the dissolution rate of meloxicam ODT, and the use of ion exchange and complexation with cyclodextrin to mask the taste of meloxicam ODT (Samprasit et al, 2013). To the authors knowledge, literature search found no study that explores the effects of different superdisintegrants on the characteristics of nano-meloxicam ODT.…”
Section: Introductionmentioning
confidence: 99%